ChemInform Abstract: Rapid Synthesis of Unsaturated Alcohols under Mild Conditions by Highly Selective Hydrogenation. Issue 49 (3rd December 2013) - Tamura, Masazumi; Tokonami, Kensuke; Nakagawa, Yoshinao; Tomishige, Keiichi
Abstract Ir/ReOx supported on silica shows high activity and selectivity in the hydrogenation of unsaturated aldehydes (I) to the corresponding unsaturated alcohols (II) at a low H2 pressure and a low temperature.